Factors affecting human performance in lathe machine shop operations - G.R, Gautham; Suresh, M; Ranganathan, Rajkumar (International Journal of Engineering and Technology, 2018)
This study helps to identify the factors, which affect human performance in lathe machine shop operations and adopt mitigation strate-gies. This study helps the practitioner to identify the critical factors that reduce human performance and occurrence of error during the opera-tions. This paper illustrates the framework development of an Interpretive Structural Modelling for analysing the factors relating to human performance in lathe machine shops. The key issues related to human performance factors are discussed and interrelationship between the factors are analysed. The results indicate that noises, temperature in work place, shop floor practice are most crucial factors.Â Â